Mobile Business Commersialization - Abdul Fikri; Arismawan Arismawan (Industrial Engineering Journal, 2015)
Smartphone shipment volumes have skyrocketed in recent years, and already overtook client PCs in 2011, 488 million smart phones, compared to 415 million client PCs. Unit sales will grow at nearly a 30% compound annual growth rate over the next five years, by 2016, it will exceed 1.5 billion units per year. It is driven by two factors, (i) replacement of nearly 5 billion feature phones with smartphones, which only make up 10% of handsets; (ii) and price declination, as International Data Corporation (IDC) suggests, from US$337 in 2013 to US$267 in 2017. In a few years, smartphones have grown from being a niche product segment at the high-end of the mobile phone market to becoming a truly mass-market proposition.